The Relationship Between the Role of Health Workers and the Provision of Reproductive Health Education and Early Marriage in the Selebar Subdistrict Work Area of Bengkulu City in 2025 - Syndi Ayu Veronica; Febra Ayudiah; Ice Rakizah Syafrie (Universitas Dehasen Bengkulu, 2026)
Bengkulu Province recorded alarming rates of child marriage under the age of 19. Data from the Regional Office of the Ministry of Religious Affairs of Bengkulu Province in 2024 showed 625 cases of child marriage under the age of 19. Seluma Regency recorded 158 cases, followed by North Bengkulu with 104 cases, Kepahiang with 79 cases, and Bengkulu City with 72 cases. These figures indicate that child marriage remains a serious problem in various regions in Bengkulu (Ministry of Religious Affairs of Bengkulu Province, 2024). The purpose of this study was to determine the relationship between the role of health workers and the provision of reproductive health education and early marriage in the Selebar District, Bengkulu City, in 2025. The study used a cross-sectional design, with data collected by distributing questionnaires to 99 married couples registered at the Office of Religious Affairs (KUA) in Selebar District, Bengkulu City, using a simple random sampling technique. Univariate analysis results indicate that the majority of respondents (65.7%) in the Selebar District Work Area, Bengkulu City, in 2025, have a positive role for health workers. Nearly half (51.5%) of respondents (51.5%) reported adequate reproductive health education, and almost all (80.8%) respondents (80.8%) did not engage in early marriage. Bivariate analysis results revealed a significant relationship between the role of health workers (p-value = 0.000) and reproductive health education (p-value = 0.001) and early marriage in the Selebar District Work Area, Bengkulu City, in 2025.Health workers should enhance their role in preventing early marriage through sustainable, structured, and easily understood reproductive health education.